PROFIT MANAGEMENT ON COMPANY PERFORMANCE : (Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2017-2019) - Ulil Maqfiroh; Nur Ika Mauliyah (Universitas Islam Balitar, 2022)
Profit is the concern of certain parties in assessing the performance of management's accountability in managing the resources entrusted to them, and can be used to estimate future prospects. The research method in this research is quantitative approach. This type of research used descriptive analysis. The data analysis techniques in this study were descriptive statistics, classical assumption test, multiple linear regression, hypothesis testing and data processing assisted by Excel and SPSS 22 version. The population of this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research observation period was carried out from 2017-2019. The research sample was taken by purposive sampling, with a total sample of 30 companies. Of the 30 companies there are 3 years of research period, so the data studied there are 90 company financial data. The results showed that (1) Real earnings management through operating cash flow partially had no effect on company performance, (2) Accrual earnings management through discretionary accruals partially affected company performance, and (3) Real earnings management and accrual earnings management partially simultaneous does not affect the company's performance.